Determinants of Financial Performance of Regional Development Banks in Java Island: Evidence from Panel Data 2020-2024 - Panggabean, Priska Basariana (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study examines the determinants of financial performance, measured by Return on Assets (ROA), among six Regional Development Banks (Bank Pembangunan Daerah/BPD) in Java Island, Indonesia, over the period 2020–2024. The sample comprises Bank DKI, Bank BJB, Bank Banten, Bank Jateng, Bank BPD DIY, and Bank Jatim. Using panel data from audited annual reports and analysed using multiple linear regression in SPSS 29, the study investigates the effects of Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), Loan-to-Deposit Ratio (LDR), and Non-Performing Loan (NPL) on ROA. The study period spans both the COVID-19 pandemic crisis of 2020–2021 and the recovery phase of 2022–2024, providing a comprehensive view of RDBs’ financial dynamics under varying macroeconomic conditions. The findings reveal that NIM has a significant positive effect on ROA, whereas CAR, LDR, and NPL do not have statistically significant individual effects; the full model explains 83.6% of the variance in ROA. These results contribute new empirical insights into the financial behaviour of Indonesian regional development banks during and after an economic crisis, with practical implications for bank management, regional government shareholders, and banking regulators.